Does activeness in organization improve English speaking skill? : University students' perspective - Kamal Yusuf; Syahrul Mabagits (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
The challenging nature of speaking English in connection to organization activeness of university students lead to some issues. The scarcity of research on that area was amongst the rationales behind conducting this present study. This study aimed to investigate students' perception on organization activeness in improving English speaking ability. A phenomenon in the background of this study indicates the significance of organizational activities fot university students and the salient of English in educational context. This study was conducted at State Islamic University of Sunan Ampel Surabaya participated by 30 students of English Education department whom have actively involved the intra or extra campus organization. The instrument used to collect data for this study was a questionnaire that has been tested for its its validity and reliability. The results of the present study revealed that the student generally demonstrated their positive reflections on that the organizational activeness contributes to improving their English speaking ability.